18β‐Glycyrrhetinic acid: its core biological properties and dermatological applications - Kowalska, A.; Kalinowska‐Lis, U. (International journal of cosmetic science, 2019)
Recently, attention has been focused on identifying natural herbal compounds with high biological activity, especially antioxidative, anti‐inflammatory and antimicrobial properties, for preventing and controlling various skin conditions, including inflammation‐related diseases such as atopic dermatitis and UV‐induced skin photoaging. One key active plant ingredient is 18β‐glycyrrhetinic acid (GA), the main metabolite of glycyrrhizin (GL), obtained from licorice root. The review examines the valuable biological properties of GA, particularly those playing key roles in the treatment of various dermatological disorders in humans. The review highlights the key anti‐inflammatory, antioxidant and antimicrobial properties of GA and its toxicity towards normal cells lines. It also examines the physicochemical properties of GA and presents methods of increasing its penetration through the stratum corneum and bioaccumulation with the use of modern delivery systems such as liposomes and nanoemulsions. Résumé Récemment, l'attention s'est concentrée sur l'identification de composés naturels à base de plantes ayant une activité biologique élevée, en particulier des propriétés antioxydantes, anti‐inflammatoires et antimicrobiennes, pour prévenir et contrôler diverses affections cutanées, y compris les maladies liées à l'inflammation telles que la dermatite atopique et le photovieillissement induit par les UV. Un ingrédient actif végétal clé est l'acide 18β‐glycyrrhétinique (GA), le principal métabolite de la glycyrrhizine (GL), obtenu à partir de la racine de réglisse. La revue examine les propriétés biologiques précieuses de l’AG, en particulier celles qui jouent un rôle clé dans le traitement de divers troubles dermatologiques chez l'homme. La revue met en évidence les propriétés anti‐inflammatoires, anti‐oxydantes et antimicrobiennes essentielles de l’AG et sa toxicité vis‐à‐vis des lignées cellulaires normales. Il examine également les propriétés physicochimiques de l’AG et présente des méthodes pour augmenter sa pénétration dans la couche cornée et sa bioaccumulation grâce à l'utilisation de systèmes d'administration modernes tels que les liposomes et les nanoémulsions. 18β‐Glycyrrhetinic Acid (GA): Pharmacological activities, e.g. anti ‐inflammatory, antioxidant, antimicrobial. Dermatological applications, e.g. contact dermatitis, acne, adverse effects of sunburns (skin ageing, hyperpigmentation). Strategies of improving GA penetration through the SC: liposomes, nanoemulsions.